2017
DOI: 10.1016/j.cell.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Reprogramming Promotes Pancreatic Cancer Metastasis

Abstract: Summary Pancreatic ductal adenocarcinoma (PDA) is one of the most lethal human malignancies, owing in part to its propensity for metastasis. Here, we used an organoid culture system to investigate how transcription and the enhancer landscape become altered during discrete stages of disease progression in a PDA mouse model. This approach revealed that the metastatic transition is accompanied by massive and recurrent alterations in enhancer activity. We implicate the pioneer factor FOXA1 as a driver of enhancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
404
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 388 publications
(427 citation statements)
references
References 61 publications
22
404
0
1
Order By: Relevance
“…PDAC metastases from distant sites were dependent on the oxidative pentose phosphate pathway for the maintenance of their malignant gene expression programs. Roe et al [34] also used a mouse PDAC model and found that the transition to a metastatic state was accompanied by massive FoxA1-driven enhancer activation. The newly activated genes rendered cells more invasive, and they assumed a cell fate resembling that of the embryonic foregut endoderm.…”
Section: Advantages Provided For Cancer Research By Cancer Cell Repromentioning
confidence: 99%
See 2 more Smart Citations
“…PDAC metastases from distant sites were dependent on the oxidative pentose phosphate pathway for the maintenance of their malignant gene expression programs. Roe et al [34] also used a mouse PDAC model and found that the transition to a metastatic state was accompanied by massive FoxA1-driven enhancer activation. The newly activated genes rendered cells more invasive, and they assumed a cell fate resembling that of the embryonic foregut endoderm.…”
Section: Advantages Provided For Cancer Research By Cancer Cell Repromentioning
confidence: 99%
“…The authors provided evidence that this tumorigenesis was caused by epigenetic reprogramming, as the oncogenic enhancers were reactivated in the cancer cell counterparts. Furthermore, recent works have illustrated an important role of the epigenetic reprogramming of chromatin modifications in the evolution of cancer metastasis [3234]. These articles emphasize the fact that reprogramming can lead to the formation of tumor-initiating cells that acquire stem cell-like phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic cancer is a lethal tumor characterized by early metastasis and a high recurrence rate, with a dismal 5-year survival rate of less than 8% [1][2][3]. Unlike many other cancers, patients remain almost symptomless in the early stage of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…These include the metastasis enhancer FOXA1 and the putative tumor suppressor FOXO6 . Interestingly, the known role of FOXA1 in the metastatic transition of pancreas cancer, originally identified in the KPC animal model used in this study, and the tumor suppressor functions of FOXO6 in lung cancer cells provide biologically plausible links to the anti-metastatic phenotype of metarrestin [3537]. …”
Section: Discussionmentioning
confidence: 99%